The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s00508-010-1397-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of oral health and 0.2% chlorhexidine oral gel on the prevalence of nosocomial infections in surgical intensive-care patients: a randomized placebo-controlled study

Abstract: Among surgical ICU patients, poor oral health had a significant positive correlation with bacterial colonization and the evolution of nosocomial infections. Oral decontamination with chlorhexidine significantly decreased oropharyngeal colonization, the incidence of nosocomial infections, length of ICU stay, and mortality in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
80
0
14

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(95 citation statements)
references
References 26 publications
1
80
0
14
Order By: Relevance
“…In three of the included studies, participants were children (Jacomo 2011; Kusahara 2012a; Sebastian 2012); in one study, participants were neonates (Stefanescu 2013); and in the remaining studies, only adults participated. In six studies, participants were either medical or surgical patients (Berry 2013;Meinberg 2012;Mo 2016;; in another five studies, participants were described as trauma patients (Grap 2011;Prendergast 2012;Scannapieco 2009;Seguin 2006;Seguin 2014); six studies recruited surgical patients only (Chen 2008;DeRiso 1996;Jacomo 2011;Kusahara 2012a;Yao 2011;Zhao 2012); nine studies recruited medical patients only (Cabov 2010;Fields 2008;Fourrier 2000;Fourrier 2005;Ozcaka 2012;Sebastian 2012;Stefanescu 2013;Tang 2013;Tantipong 2008); and in the remaining 12 studies, it was not clearly stated whether participants were medical, surgical, or trauma cases. Nine of the included studies (Fields 2008;Fourrier 2000;Grap 2011;Lorente 2012;Ozcaka 2012;Pobo 2009;Prendergast 2012;Roca Biosca 2011) specifically excluded edentulous participants, and the remaining studies did not report whether or not participants were dentate.…”
Section: Participantsmentioning
confidence: 99%
See 4 more Smart Citations
“…In three of the included studies, participants were children (Jacomo 2011; Kusahara 2012a; Sebastian 2012); in one study, participants were neonates (Stefanescu 2013); and in the remaining studies, only adults participated. In six studies, participants were either medical or surgical patients (Berry 2013;Meinberg 2012;Mo 2016;; in another five studies, participants were described as trauma patients (Grap 2011;Prendergast 2012;Scannapieco 2009;Seguin 2006;Seguin 2014); six studies recruited surgical patients only (Chen 2008;DeRiso 1996;Jacomo 2011;Kusahara 2012a;Yao 2011;Zhao 2012); nine studies recruited medical patients only (Cabov 2010;Fields 2008;Fourrier 2000;Fourrier 2005;Ozcaka 2012;Sebastian 2012;Stefanescu 2013;Tang 2013;Tantipong 2008); and in the remaining 12 studies, it was not clearly stated whether participants were medical, surgical, or trauma cases. Nine of the included studies (Fields 2008;Fourrier 2000;Grap 2011;Lorente 2012;Ozcaka 2012;Pobo 2009;Prendergast 2012;Roca Biosca 2011) specifically excluded edentulous participants, and the remaining studies did not report whether or not participants were dentate.…”
Section: Participantsmentioning
confidence: 99%
“…VAP was fully reported by 34 of the included studies (Bellissimo-Rodrigues 2009;Berry 2013;Bopp 2006;Cabov 2010;Caruso 2009;Chen 2008;DeRiso 1996;Feng 2012;Fourrier 2005;Grap 2011;Hu 2009;Jacomo 2011;Kusahara 2012a;Long 2012;Lorente 2012;Meinberg 2012;Mo 2016;Ozcaka 2012;Pobo 2009;Prendergast 2012;Scannapieco 2009;Sebastian 2012;Seguin 2006;Seguin 2014;Stefanescu 2013;Tang 2013;Tantipong 2008;Xu 2007;Xu 2008;Yao 2011;Zhao 2012). One study reported only that there was no difference in VAP between the two arms of the study (Roca Biosca 2011).…”
Section: Incidence Of Vapmentioning
confidence: 99%
See 3 more Smart Citations